Two Lugar Houses in Galloway. Issue 1 (November 2017) - Wolffe, Antony; Agnew, Richard
Abstract : This article is a study of two houses in the Stewartry of Kirkcudbright which were both designed by Robert Lugar in the 1820s. Hensol and Glenlee Park are about eight miles apart in the valley of the River Ken, to the south and north of New Galloway respectively. The two clients were John Cuninghame (at Hensol) and his older sister Anne, Lady Ashburton (at Glenlee Park). One was an eligible bachelor and the other an eligible, childless widow. Stylistically, however, the two houses are very different. Glenlee Park, where Lugar added to an existing house, is austerely neo-classical with interesting hints of Nash's work, whereas Hensol is an entirely new house in Tudor Gothic style on the Duchrae estate that previously lacked a laird's house. In spite of modifications and alterations much of Lugar's work at both houses has survived to the present day. This article examines the background to the building of both houses and what is known of the two clients, within the wider context of Lugar's career. It also outlines the subsequent architectural history of the two houses. One of the authors has been professionally involved as an architect with both houses while the other is the present owner of Glenlee Park.